This equation has one solution. 3(x – 2) + 4x = 10(x + 1) What is the solution? A.–5 B.–2 C.StartFraction negative 16 Over 3 EndFraction D.StartFraction negative 16 Over 7 EndFraction

Answer :

Answer:

-16/3 = x

Step-by-step explanation:

3(x – 2) + 4x = 10(x + 1)

Distribute

3x -6 +4x = 10x+10

Combine like terms

7x-6 = 10x+10

Subtract 7x from each side

-6 = 3x+10

Subtract 10 from each side

-16 = 3x

Divide by 3

-16/3 = 3x/3

-16/3 = x

Answer:

x = -16/3

Step-by-step explanation:

All work is in the image below!

${teks-lihat-gambar} Аноним

Other Questions